Adult development and aging : biopsychosocial perspectives - Whitbourne, Susan Krauss; Whitbourne, Stacey B.; Whitbourne, Susan Krauss (Hoboken, NJ : Wiley, 2011)
"The fourth edition continues to provide psychologists with a fresh and engaging approach to the field of psychology of adult development and aging. It focuses on three themes: a multidisciplinary approach, positive images of aging, and the newest and most relevant research. Recent articles and updates to the information on demography, economics, and public policy are presented. The Aging in the News feature includes a story of a remarkable achievement by a middle-aged or older adult. The Assess Yourself boxes are also updated with new questions. Psychologists appreciate this mix of examples and discussions that make the material come to life."--
Machine generated contents note: Chapter 1: Themes and issues in adult development and aging -- Chapter 2: Models of development: nature and nurture in adulthood -- Chapter 3: The study of adult development and aging: research methods -- Chapter 4: Physical changes -- Chapter 5: Health and prevention -- Chapter 6: Basic Cognitive Functions: Information processing, attention, and memory -- Chapter 7: Language, Problem-Solving, and Intelligence -- Chapter 8: Personality -- Chapter 9: Relationships -- Chapter 10: Work, Retirement, and Leisure Patterns -- Chapter 11: Mental Health Issues and Treatment -- Chapter 12: Long-Term Care -- Chapter 13: Death and Dying -- Chapter 14: Successful Aging.
Rev. ed. of: Adult development & aging, c2010.
Includes bibliographical references (p. 333-378) and indexes.
Keywords: Gerontology; Older people -- Psychology; Older people -- Health and hygiene; Older people -- Social conditions